2021
DOI: 10.52547/ijes.4.4.60
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Work Family Enrichment on Job Satisfaction and Family Satisfaction: The Moderating Role of Affectivity

Abstract: Purpose: The purpose of this study is to investigate the effect of both work to family enrichment and family to work enrichment on family satisfaction and work satisfaction. The moderating role of positive and negative affectivity is also examined in this regard. Methodology: This Study is an empirical survey research with the statistical population of faculty members of Iran's universities. The research questionnaires were distributed among professors of five premier universities of Tehran. 200 people were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(60 reference statements)
0
0
0
Order By: Relevance
“…Similarly, (Zhang 2013) found that men had a stronger and more positive relationship than women between job involvement and organizational citizenship behaviour. Other studies have identified, on the contrary, that gender is not a determinant of job involvement (Ebrahimi 2021;Kim et al 2018).…”
Section: Job Involvement and Job Performancementioning
confidence: 95%
“…Similarly, (Zhang 2013) found that men had a stronger and more positive relationship than women between job involvement and organizational citizenship behaviour. Other studies have identified, on the contrary, that gender is not a determinant of job involvement (Ebrahimi 2021;Kim et al 2018).…”
Section: Job Involvement and Job Performancementioning
confidence: 95%